Informática aplicada à educação no município de Belém: a visão do professor sobre o trabalho com as tecnologias digitais - Costa, Andrea Lilian Marques da (2013)
This study describes and analyzes the obstacles to the effective implementation of informatics applied to education in the schools of the state of Pará, in Belém, taking as variables the working conditions of teachers, the pedagogical model of deployment and teacher training that has been established in recent years. The study stems from the understanding that there lies with the information technology and communication (ICT) a mediating role for the realization of educational goals in school, so that this process will result in the enrichment of the transmission / construction / assimilation of school knowledge. However, although there is a rich set of tools that can be used in this perspective, the truth is that their promised effects and substantial changes have not happened yet. Research and indexes resulting from national tests fail to show the changes. This research is being carried out from the perspective of locating the reason that underlies the difficulties of implementation and verification of effective entry of computers in school. It is adopted as a theoretical historical-critical pedagogy, pedagogical theory that provides elements that can critically understand the school as an instrument to help overcome the marginalization, through the universalization of the cultural patrimony of humanity. Research is carried out with a sample of 13 basic education schools in the city of Belém. The work includes analysis of official documents related to the use of ICT, as well as interviews with teachers, managers and professionals involved in administrative positions related to the use of ICT in education. The inequalities of the schools involved can be perceived in the implementation process of the computer rooms in the school environment. In the face of the findings of this research, about the poor working conditions, inadequate training for use of ICT as a teaching resource, the availability of computer rooms without the minimum structure for operation, it is stated that the assumption of "resistance", "fear the new", "stay in the comfort zone" and similar ideas, as alleged causes of the widespread lack of effectiveness in teaching supported by ICT, should not be accepted, much less adopted as an explanation of the reality of the difficulty of teaching with ICT